Graphene Effect on Efficiency of TiO2-based Dye Sensitized Solar Cells (DSSC) - Ha, Nguyen Thai; Long, Pham Duy; Trung, Nguyen Thanh; Hong, Le Van (Communications in Physics, 2016)
Colloidal paste of TiO2 embedded with graphene (GS) was fabricated and used to spread TiO\(_2\) film photo-electrode of DSSC solar cells. The dye N179 and Iodine-based electrolyte were used in the DSSC solar cells. Raman scattering, SEM images were used to identify the material phases and microstructure of the film photo-electrode. I/V characteristics of the DSSC cells were recorded at room temperature. Open-circuit voltage Voc, short-current \(J_sc\) and efficiency η of the DSSC cells were estimated. It shows that graphene addition has affected on \(V_oc\),\(J_sc\) and \(η\). The \(V_oc\),\(J_sc\) and \(η\) abnormally depend on graphene content. The efficiency reached a maximal value with graphen concentration of 0.005 wt %, after that decreased. It is supposed to be related with an improving the charge transfer in the working photo-electrode of DSSC.